Fabrication and characterization of ONO and tunnel oxide for 16k FLOTOX EEPROM cell - Hashim, U.; Ayub, R.M.; On, K.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The EEPROM process is one the hardest process to be developed. The performance of the EEPROM devices is normally judged on the programming speed, which relates to program high (erase) and program low (write) operations. It is essential that the program high and program low speed of the EEPROM cell is within 1ms with a programming voltage of not more than 16V. In this study, two experiments were setup to improve the programming speed. The first experiment was to increase the high voltage NMOS drain junction breakdown voltage with the source floating (HVNMOS BVDSF), and the second experiment was to scale down the ONO layer. The characterization work to increase the programming speed of the memory cell of 16k FLOTOX EEPROM has been carried out. P-field implant dose is optimized to have both the HVNMOS BVDSF and the p-field threshold voltage above 16V for fast programming. As a result, the threshold voltages of programming high and low operation are achieved at 4.35V and -0.77V respectively. Furthermore, by scaling down the nitride layer of ONO from 160A to 130A, the Vt program window is further improved to 4.5V and -0.94V for the program high and program low operations respectively.